Adipose tissue, friend or enemy? (Gaceta de Ciencias Veterinarias, 2021)
Obesity is a chronic disease characterized by an increase in body fat or White Adipose Tissue (WAT), which, depending on its magnitude and anatomical location, will determine health risks that limit expectations and quality of life. In companion animals such as dogs and cats, castration, lack of physical activity, inadequate nutrition, together with the breed, are the cause of the increase in the development of this condition, which predisposes pathophysiological states such as insulin resistance, syndrome metabolic, cardiovascular diseases and type II diabetes mellitus. Basically, obesity arises from an excess in caloric intake against a low energy expenditure caused by a sedentary lifestyle and overeating, situations that promote hypertrophy and excessive hyperplasia of WAT.